Integrating self-awareness surveys and ovitrap monitoring to enhance dengue vector control: A community-based experimental study in Bulusan Village, Semarang City - Kushartanti, Roro; Fitriana, Nur Gilang (CORE JOURNAL, 2025)
Previous studies on Dengue Hemorrhagic Fever (DHF) prevention have often emphasized knowledge dissemination and community participation without directly linking these behavioral interventions to measurable entomological outcomes. There remains a gap in evidence regarding the integration of self-awareness strategies with vector surveillance indicators such as the Container Index (CI) and the Free Larvae Index (ABJ). This study aimed to evaluate the effectiveness of a community-based self-awareness survey combined with ovitrap training in controlling mosquito breeding as a preventive measure against DHF in Bulusan Village, Semarang City. This descriptive observational experimental study involved households selected through incidental sampling during routine Mosquito Nest Eradication (PSN) activities. Participants received training on installing simple ovitraps made from various household materials, which were monitored over one to two weeks. Entomological outcomes were assessed using CI and ABJ, supported by environmental observations and household interviews. The results revealed that all ovitrap types successfully detected mosquito larvae, with mineral water containers showing the highest Container Index (12.5%). This intervention led to an increase in ABJ, indicating improved mosquito control practices. The integration of behavioral self-awareness tools with low-cost entomological surveillance offers a promising model for community empowerment in DHF prevention. These findings suggest that collaborative efforts between communities and local health stakeholders can strengthen sustainable and environmentally friendly vector control strategies, particularly in endemic urban settings.